Automated Improvement for Component Reuse - Ramachandran, Muthu (INFOCOMP Journal of Computer Science, 2004)
Software component reuse is the key to significant gains in productivity. However, the major problem is the lack of identifying and developing potentially reusable components. This paper concentrates on our approach to the development of reusable software components. A prototype tool has been developed, known as the Reuse Assessor and Improver System (RAIS) which can interactively identify, analyse, assess, and modify abstractions, attributes and architectures that support reuse. Practical and objective reuse guidelines are used to represent reuse knowledge and to do domain analysis. It takes existing components, provides systematic reuse assessment which is based on reuse advice and analysis, and produces components that are improved for reuse. Our work on guidelines has been extended to a large scale industrial application.